Representation Needs Resistance. Issue 1 (2nd January 2017) - Hamilton, Lawrence
Abstract : In responding to the five excellent articles on Freedom Is Power collected here, I argue that my account of representation in politics runs all the way down, as does my associated views on needs and institutional critique aimed at diminishing domination. I take on board some of the other criticisms levelled at me, but resist the notion that my account of freedom as power constrains resistance. Liberty through representation requires and depends upon resistance; it also institutionalises it.